A trip across art therapy - Coll Espinosa, Francisco J. (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2006)
The process in art therapy is described as a trip from own known territories to new others. It is a trip of creation in a safety context and a space of intimacy shared with the art therapist, where the participant goes away towards unknowed of himself, joining reason, emotion and intimacy.